Pengaruh Tingkat Pendidikan dan Pengalaman Kerja Terhadap Produksi Industri Rumah Tangga Mebel di Kecamatan Pancur Kabupaten Rembang - Junarti Junarti; Parikesit Penangsang (Pusat Riset dan Inovasi Nasional, 2024)
Pancur sub-district is an area that has great potential in the wooden furniture household industry. In the Pancur sub-district, the wooden household furniture industry is very easy to find because almost every village has household-scale furniture production. In carrying out household furniture industry production, education and work experience are pending factors in the production process. Low levels of education and work experience in the furniture industry can be a problem in production. Therefore, the aim of this research is to find out how work experience and education level influence the production of home furniture industry in Pancur sub-district, Rembang district. The quantitative descriptive method used in this research is multiple linear regression analysis. The research results show that the level of education does not have a significant impact on furniture production. furniture in the home industry, on the other hand, work experience influences the production of the home furniture industry. However, together the level of education and work experience has a significant influence. This is because the level of education can strengthen the level of work experience.